Motility and Viability of Nunukan Chicken Spermatozoa in Egg Yolk-Skim Milk Diluent with the Addition of Various Glucose Levels as an Energy Source - Indana, Khoiru; Anjani, Fandini Meilia; Ardiansyah, Ardiansyah (CV. Komunitas Dunia Peternakan, 2024)
This study aims to determine the effect of adding glucose to skim milk diluent on the motility and viability of nunukan chicken spermatozoa. The materials used are fresh semen from 20 male Nunukan chickens aged 1-2 years, glucose 2%, 3%, and 4%, egg yolk, skim milk, and distilled water. The research design used in this research is a Completely Randomized Design (CRD) with four treatments and five replications. The data obtained will then be analyzed using variance (ANOVA). The treatments were P0 with semen + skim milk without adding glucose, P1 = cement + skim milk + 2% glucose, P2 = cement + skim milk + 3% glucose, P3 = cement + skim milk + 4% glucose. The results showed that the percentage of sperm motility of nunukan chickens from all treatments showed significantly different results (P<0.05). It can be concluded that adding 3% glucose to skim milk diluent provides optimal motility and viability of nunukan chicken spermatozoa.